Study of Magnetic and Dielectric Properties of Nano-Crystalline Mn-Substituted Zn Ferrites - Roaa R. Ahmed (Academic Science Journal)
In the present work, zinc substituted manganese nano ferrites, Mn1-xZnxFe2O4 ferrites with x variable from (0.3,0.7 and 0.9) synthesized by co-precipitation method. To investigate the dielectric characteristics of each sample with relation to frequency. With rising frequency, the loss tangent and the dielectric constant both rapidly decrease before stabilizing at higher frequencies, exhibiting normal ferromagnetic behavior were studied in the frequency range (50Hz -5 MHz). On the basis of XRD, the effect of zinc concentration on Mn1-x Znx Fe2O4 particle size has been addressed. By using Cu-K radiations in combination with X-ray diffraction, the crystalline phases have been found. The XRD patterns have shown that the specimen has spinal type structure, at room temperature and the particle size decreases with concentrations zinc increasing. Effect of varying concentrations of x on the spontaneous magnetization of distinct Mn1-x Znx Fe2O4 sample is determined. All of the samples of ferrites were magnetic, either of low or high magnetization, according to our findings. At x=0.9 and x=0.3 respectively. The maximum spontaneous magnetization and the smallest particle size were attained. Hysteresis loops of the materials show exhibit nanocrystals ferromagnetic behavior. The magnetic properties were explained in terms of cation distribution and the effect of grain size.